Haptic Recognition of Familiar Objects: Examining Lateralization of Specificity Effects. Issue 2 (October 2014) - González-Alvarez, Julio; Palomar-García, María-ángeles
Previous research has found evidence in favor of two subsystems underlying object recognition: an abstract-category subsystem that mainly works in the left hemisphere (LH) and a specific-exemplar subsystem that mainly works in the right hemisphere (RH). This asymmetry has been observed in both the visual and auditory domains by means of long-term repetition priming experiments. This study explored whether this asymmetrical pattern extends to the haptic domain through an experiment in which 30 right-handed participants (24 women) ages 18 to 38 years could identify familiar objects with a single hand. The procedure included two blocks of trials, the study (presentation of primes) and the test phase (presentation of targets), separated by a short distractor task. Of interest was if repetition of the same exemplar object (e.g., the same cigarette lighter) produced more priming than repetition of a different exemplar of the same object category (e.g., a different cigarette lighter), and, crucially, if this hypothetical same-exemplar advantage (specificity) was larger when objects were identified with the left hand (RH). An ANOVA was performed on RTs with priming type (same-exemplar primed, different-exemplar primed and unprimed) and hand (left, right) as within-participants factors. Results showed a main effect of priming type due to a same-exemplar advantage (shorter RTs) both for the left and the right hand, but a non-significant interaction between specificity effects and hands.